Exchange and Political Communication: Study at Regent Election of Soppeng District - Rosmawati Rosmawati; Harifuddin Harifuddin; Sudirman Sudirman (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract: This paper aims to reveal the socio-political reality that is loaded with interest. The interest certainly are mutually-beneficial but often unbalanced political advantage. In this regard, politics always intersect or identical to ‘exchange’ and ‘communication’. When interpreted in reverse, that isn’t politics if it doesn’t contain elements of ‘exchange’ which must be preceded by a communication strategy its politicians. Specifi cally, this paper reveals the occurrence of a ‘political exchange’ and the ongoing process of ‘political communication’. Set in the elections in Soppeng district iIn 2010, the process of exchange and political communication that takes place generally is ‘transactional’. Although some cases of ‘looks’ is ‘interactional’ but it always ends with a political compensation (transactional).Keywords: Exchange, Political Communication, Election, Transactional, Interactional